Lipid Metabolism: Immune Regulation and Therapeutic Prospectives in Systemic Lupus Erythematosus - Sun, Wei; Li, Pengchong; Cai, Jianping; Ma, Jie; Zhang, Xuan; Song, Yong; Liu, Yudong (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a heterogeneous disease characterized by the production of abnormal autoantibodies and immune complexes that can affect the organ and organ systems, particularly the kidneys and the cardiovascular system. Emerging evidence suggests that dysregulated lipid metabolism, especially in key effector cells, such as T cells, B cells, and innate immune cells, exerts complex effects on the pathogenesis and progression of SLE. Beyond their important roles as membrane components and energy storage, different lipids can also modulate different cellular processes, such as proliferation, differentiation, and survival. In this review, we summarize altered lipid metabolism and the associated mechanisms involved in the pathogenesis and progression of SLE. Furthermore, we discuss the recent progress in the role of lipid metabolism as a potential therapeutic target in SLE.